Kontribusi Desa Wisata Sendang Duwur Kabupaten Lamongan Terhadap Ekonomi Masyarakat Lokal - Silaban, Ursulla Mariska Maduma; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 6 No 2 (2018): VOL 6, NO 2 (2018): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2019)
Location of this research in Sendang Duwur district of Lamongan. The condition of tourism Sendang Duwur Village have big potential in giving economic contribution to local society. This is the purpose of this research. Based on the above research that revealed three problems, namely what the uniqueness from tourism product in Sendang Duwur Village, how was the tourist shopping behavior in Sendang Duwur Tourism Village, And how was contribution of Sendang Duwur Tourism Village for Local Comunnity Economic. To express the above problem this research using primary and secondary data source, while type of data used is the qualitative data and quantitative data. The technique in order to obtain the validity of data using flow model method and quantitative analyzing. Data which collect by questionnaire, in-depht interview, observation and documentation. The results of this study related to tourism product unique of Sendang Duwur Tourism Village as attraction, amenities, accessibility and ancillary services. The type of tourist shopping behavior is tourist who like to look for variety with percentage of 80%. Sendang Duwur Tourism Village has not contributed optimally to improve community local economic because visitor spending whose amount is determind by length of stay cannot be used because there is no tourist staying. Tourist only make shorts visit. Some advice will be given for the local people so that keep specificity of tourism product. For the government to more active to promote Sendang Duwur Village to be known to many people.   Keywords : contribution economy, tourism village, local community